2012
DOI: 10.1038/msb.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of genome, transcriptome and proteome reveals the response to aneuploidy in human cells

Abstract: Genomic, transcriptomic and proteomic profiles of human aneuploid cells reveal that mRNA levels increase with gene copy number, but protein levels are partially compensated. Aneuploid cells also exhibit common alterations in several pathways, including an activation of autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
143
126
76
25

Citation Types

64
579
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
337
131
75
70

Relationship

22
399

Authors

Journals

citations
Cited by 421 publications
(645 citation statements)
references
References 35 publications
(54 reference statements)
64
579
0
2
Order By: Relevance
“…Systematic introduction of extra chromosomes into yeast genomes revealed that single chromosome gains lead to slower proliferation and various detrimental metabolic and physiological consequences 7 . Studies in mouse and human cell lines reached similar conclusions: single chromosome gains generally impair proliferation, alter metabolism and induce various stress responses 8,16 . Further, oncogene-transformed trisomic cells exhibit reduced tumorigenicity compared to their diploid counterparts 5 .…”
Section: Is Aneuploidy Tumor-promoting or Tumor-suppressive?mentioning
confidence: 67%
“…The answer to such questions is not straight-forward. Single trisomies are sufficient to significantly affect cellular functions 5,16,28 and are, by the classical definition, aneuploid. However, at the same time, when tumors with single chromosome gains or losses are classified in the "diploid" group, the prognostic value of high degree of aneuploidy becomes stronger 29 .…”
Section: Defining Aneuploidymentioning
confidence: 99%
See 1 more Smart Citation
“…Another finding for both pairs was that the downregulated genes was dominant in the term of “transcription regulator activity” (χ 2 test, P < 0.01), consistent with the fact of a priority of downregulated gene expression. However, in term of “translation regulator activity,” the upregulated genes manifested booming (χ 2 test, P < 0.01), strengthening the idea that some transcript expression profilings would be adjusted at the process of translation (Stingele et al, 2012 ). It seemed likely that the sophisticated mechanisms responding to deficiency of C2 not only functioned at the beginning of transcription but also threaded throughout the process of gene expression.…”
Section: Resultsmentioning
confidence: 83%
“…This may explain why these genes also directly contribute to embryonic development, including "nervous system development", "heart and skeletal muscle development" and "face morphogenesis", indicating a close correlation between altered cellular processes and dysplastic phenotypes manifested in DS fetuses. In contrast, downregulated genes principally affect "DNA replication and cell cycle", which was revealed as a shared phenotype among multiple aneuploids [36]. Indeed, the downregulated genes may result from the upregulated genes, in other words, the upregulated genes disrupted the developmental program and consequently led to defects in cell proliferation in DS, which was confirmed through proliferation assay using EdU staining (Supplementary Figure 4B, 4C).…”
Section: Discussionmentioning
confidence: 81%
“…Annotations related to inflammatory and stress responses and extracellular regions are upregulated in all mammalian model aneuploid cells, whereas lysosomes, vacuoles and membrane metabolism are consistently upregulated only in human aneuploids. The deregulated pathways determined by transcriptome analysis largely overlap with the proteome analysis performed in model human aneuploid cell lines . These findings suggest a model in which changes in expression throughout the whole genome are largely driven by aneuploidy per se .…”
Section: Transcriptome and Proteome Response To Whole Chromosome Aneumentioning
confidence: 71%
“…It should be noted that the environmental stress response reflects changes in the cell‐cycle distribution rather than a genuine stress response ; thus, identification of the environmental stress response in aneuploid cells further emphasizes the marked negative effect of de novo aneuploidy on cell‐cycle progression. Aneuploid mammalian cells and amniocytes from trisomic pregnancies also show uniform aneuploidy‐driven pathway deregulation . Gene ontology terms associated with DNA and RNA pathways such as DNA replication, repair, chromosome condensation and segregation, cell‐cycle progression, ribosome biogenesis and RNA processing were consistently downregulated in human and mouse aneuploid cell lines .…”
Section: Transcriptome and Proteome Response To Whole Chromosome Aneumentioning
confidence: 97%
See 7 more Smart Citations
“…These findings resonate with an earlier study using a fly brain tumor model (Jü schke et al, 2013), which showed that levels of proteins participating in common complexes were more strongly controlled than their matching mRNAs. Consistently, studies in breast cancer cells and yeast cells have shown that stable protein complexes tend to maintain constant protein expression, despite changed gene copy number and mRNA levels (Dephoure et al, 2014;Geiger et al, 2010;Stingele et al, 2012). Thus, molecular requirements such as protein complex stoichiometry seem to constrain protein level variation in somatically mutated cells more strongly than transcript variation.…”
Section: Relative and Absolute Concentration Regulation Of High-abundmentioning
confidence: 74%
“…Indeed, it seems difficult to imagine a generic (i.e., non-gene-specific) process by which translation rates could be adapted to erroneous mRNA levels (Bader et al, 2015). Thus, adaptation of protein turnover through protein degradation remains as a plausible candidate process (Battle et al, 2015;Stingele et al, 2012). It is well established that the stoichiometry of ribosomal proteins is controlled via degradation of excess proteins that cannot be incorporated into ribosomes (A) Buffering of protein levels against mRNA variation can occur at multiple scales, including intra-and inter-individual genomic variation, as well as interspecies variation.…”
Section: Adaptation Of Translation Rates Does Not Fully Explain Buffementioning
confidence: 99%
“…This primary dosage effect due to trisomy may cause secondary transcriptional changes through trans-acting factors and proteomic stress response. 77,78 This observation offers an explanation for the shared dysregulated pathways and phenotypes across different trisomic cells. 18,44 Previous imaging studies of trisomic cells reported chromosome compaction in either trisomic chromosomes 34 or disomic chromosomes.…”
Section: Discussionmentioning
confidence: 87%
“…Consistent with previous studies, 73 we observed the transcriptional upregulation of trisomic chromosomes. This primary dosage effect due to trisomy may cause secondary transcriptional changes through trans‐acting factors and proteomic stress response 77,78 . This observation offers an explanation for the shared dysregulated pathways and phenotypes across different trisomic cells 18,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of HCT116 and RPE cells with one or two additional chromosomes revealed that, while transcription reflects gene copy number, protein levels for ~25% of genes on the extra chromosomes are lower than what would be predicted based on gene copy number and are instead similar to the levels in diploid cells (Stingele et al, 2012). Proteins whose expression was downregulated post-transcriptionally included those that function in DNA replication and repair, which is consistent with the observed growth defect during interphase, as well as with a delay in DNA synthesis (Passerini et al, 2016).…”
Section: The Aneuploidy Paradoxmentioning
confidence: 79%
“…Consistent with this, trisomy 21 patients have reduced stature and head circumference (Van Gameren-Oosterom et al, 2012). HCT116 cells with extra copies of chromosome 3 or 5 also showed marked growth delay under standard conditions (Stingele et al, 2012). Therefore in yeast, mice, and human, chromosome gains confer a growth disadvantage under conditions optimized for euploid cell growth.…”
Section: The Aneuploidy Paradoxmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, genes involved in carbohydrate metabolism displayed decreased expression. A similar but not identical response was found in human cells when comparing DNA, mRNA, and protein levels of euploid and aneuploid human cell lines [6]. For this purpose, multiple human tri-and tetrasomic cell lines were transcriptionally profiled and compared to aneuploid human cancer cell lines.…”
Section: Gene Expression Changesmentioning
confidence: 80%
“…Finally, autophagy, a process that removes surplus and damaged proteins and organelles, is upregulated in aneuploid cells [6]. Stable aneuploid human colon cancer cells display increased numbers of LC3 foci, an autophagy marker [43], and upregulated p62-dependent autophagy.…”
Section: Proteotoxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…It has been proposed that cells respond to aneuploidy by engaging proteotoxic stress response, which includes upregulation of pathways leading to the degradation of cellular constituents and protein folding 30 . Specifically, upregulation of autophagy was observed consistently in aneuploid cells 28 . We exploited single-cell analysis to show for the first time that TTFields application specifically triggers autophagy in the progeny cells that divided during treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Abnormal mitosis following TTFields application results in different cell fates including the formation of aneuploid daughter cells 7 , 8 . Aneuploidy is associated with the activation of regulators of autophagic and lysosomal gene expression 27 , 28 . To explore whether autophagy was more prominent in cells that divided during TTFields application, we analyzed autophagosome dynamics within single cells using U-87 MG cell line stably expressing LC3 protein fused with green fluorescent protein (GFP).…”
Section: Resultsmentioning
confidence: 99%
“…There was no overlap among genes deregulated in each of these trisomies, possibly consistent with the trans-effect seen in aneuploid yeast strains. More recent microarray-based measurements of gene expression in trisomic MEFs [32] and trisomic HCT116 cells [31] also agree that the level for most transcripts expressed from aneuploid chromosomes varies proportionally to the copy number of that chromosome. Nevertheless, as in DLD1 cells [30], few deregulated genes located on various chromosomes were also found.…”
Section: Effect Of Aneuploidy On the Gene Expressionmentioning
confidence: 82%
“…However, about 25% of proteins encoded on aneuploid chromosomes were found in lower amounts than expected based on the chromosome copy number. Protein kinases and components of large macromolecular complexes were over-represented among the latter category [31]. This observation suggests that there may be mechanisms that correct for the altered component stoichiometry of protein complex.…”
Section: Effect Of Aneuploidy On the Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations